Korea's unique alphabet (Korea Selection, 2010)
Hangeul, the indigenous writing system of Korea, was promulgated in 1446. It is an ingenious system that utilizes modern and scientific linguistic theories and principles of Korean traditional culture to perfectly express the sounds of the Korean language. Crafted by some of the leading scholars of the age, including the brilliant King Sejong the Great, the alphabet has been widely lauded by scholars the world over for its advanced phonetic system and ease of use.
Keywords: Korean language,Tiếng Hàn Quốc; Alphabet,Bảng chữ cái